Abstract of genus Poa L. (Poaceae Barnhart) in Kazakh Altai, Saur-Manrak and Zaisan valley (Experimental biology, 2018)
The abstract of the genusPoa L. was compiled by the authors on the basis of field expedition work in 1970-2010 years, and also on the collections of other collectors stored in the herbarium of the republican state enterprise on the right of economic management ‘Altai Botanical Garden’ (c. Ridder) and of the republican state enterprise on the right of economic management‘Institute of Botany’and fitointroduction (c. Almaty). Aim: Specification of the species composition and distribution of species of the Poa genus (fam. Poacaeae Barnhat) in the territory of the Kazakhstan Altai, ridges that suround Altai and the Zaisan hollov. Was established 33 species from 2 subgenera, 7 sections, of which 7 species are new to the flora of Kazakhstan on the investigated territory. The saturation of the genus Poa L. of the total number of species in the Central Altai is 45.5% (15 species), the Southern Altai - 57.6% (19 species), the Kalbinsky Altai - 33.3% (11 species), Saur-Manrak - 33.3% (11 species), Zaisan valley - 15.2% (5 species). The Poa subgenus is represented systematically by 30 species (90.9%); subgenus Arctopoa (Griseb.) Probat.includes 3 types. The nature of life forms is dominated by the dense sod - 14 (42.4%), loose sod - 14 (42.4%) species. In the ecological plan, the greatest number of species is represented by mesophytes (48.5%). According to the results of research, the species composition of the genus Poa L. of Kazakhstan is supplemented with 7 species: Poaalpigena (Fries) Lindman, Poa sergievskajae Probat., Poa veresczaginii Tzvel., Poa glauca Vahl, Poa krylovii Reverd., Poa argunensis Roshev., Poa pseudoaltaica (Olonova) Olonova).